The Effect of Green Human Resource Management Practices on Corporate Reputation: The Mediating Role of Talent Attraction and Retention in Yogyakarta Hotels - Murniady Muchran; Sri Handari Wahyuningsih; Iqbal Aditya Haqi (UPY Business and Management Journal (UMBJ), 2026)
Purpose: This study examines the direct and indirect effects of Green Human Resource Management (GHRM) practices on corporate reputation through talent attraction and talent retention in the hospitality industry. The study specifically addresses the limited understanding of how sustainability-oriented HR practices are translated into reputational outcomes through human capital mechanisms in service-intensive industries. Methodology: A quantitative research design was employed using survey data collected from 177 managers of four- and five-star hotels in Yogyakarta, Indonesia. The data were analyzed using structural equation modeling. Findings: The results reveal that GHRM practices does not have a direct effect on corporate reputation. However, it exerts a significant indirect influence through talent attraction and talent retention, which function as key mediating mechanisms. These findings suggest that the reputational value of GHRM practices emerges through talent-based organizational mechanisms, not through direct organizational effects. Implications: Theoretically, this study extends the GHRM practices and corporate reputation literature by elucidating the human capital pathways through which sustainability-oriented HR practices enhance organizational legitimacy in a developing country context. Practically, the findings suggest that hospitality organizations should align GHRM initiatives with employer branding and employee retention strategies to achieve reputational advantages. Originality: This research contributes to the literature by positioning talent attraction and talent retention as strategic mediating mechanisms linking environmentally oriented HR practices and corporate reputation in the hospitality industry. The study further highlights that corporate reputation may be strengthened indirectly through talent-based mechanisms rather than through direct implementation of GHRM practices alone.